Magnetic Nanoparticles as a Support for a Copper (Ii) Complex with Nuclease Activity - Lemus-Chavez, L; Lemus-Chavez, L; Casagrande-Denardin, J (Elsevier Inc., 2018)
Magnetic nanoparticles have been extensively explored for the development of platforms for drug delivery and imaging probes. In this work, we have used a modular capping strategy to produce magnetic gold-coated Fe 3 O 4 (Fe 3 O 4 @Au) nanoparticles, which have been decorated with a copper (II) complex containing a thioether derivative of clip-phen (Fe 3 O 4 @Au@Cu), where the complex [Cu(2CP-Bz-SMe)] 2+ has affinity to bind DNA and proven nuclease activity (2CP-Bz-SMe=1,3-bis((1,10-phenanthrolin-2-yl)oxy)-N-(4-(methylthio)benzylidene)propan-2-imine). The functionalization of Fe 3 O 4 @Au with the copper complex occurs through the sulfur atom of the thioether moiety, as indicated by Raman scattering on surface. The magnetic measurements showed the nanomaterial Fe 3 O 4 @Au@Cu is still magnetic although the gold shell and the functionalization with the copper complex have diminished the magnetization due to the dilution of the magnetic core. The nuclease assays performed with Fe 3 O 4 @Au@Cu indicate that the nuclease activity of the nanomaterial toward the plasmid DNA involves an oxidative pathway in which H 2 O 2 species is involved as intermediate in a Fenton-like reaction. Based on the electron paramagnetic resonance spectra (a N = 15.07 G, a H = 14.99 G), such nuclease activity is assigned, essentially, to the HO[rad] species indicating that the radical production property of [Cu(2CP-Bz-SMe)] 2+ is successfully transferred to the core-shell gold-coated Fe 3 O 4 magnetic nanoparticles. To the best of our knowledge, this is the first study reporting nuclease activity due to the reactive oxygen species generated by a copper complex immobilized on a gold-coated magnetic nanoparticle. © 2018 Elsevier Inc.